2003
DOI: 10.1152/japplphysiol.00552.2002
|View full text |Cite
|
Sign up to set email alerts
|

Selected Contribution: Neuroplasticity in nucleus tractus solitarius neurons after episodic ozone exposure in infant primates

Abstract: Acute ozone exposure evokes adverse respiratory responses, particularly in children. With repeated ozone exposures, however, despite the persistent lung inflammation and increased sensory nerve excitability, the central nervous system reflex responses, i.e., rapid shallow breathing and decreased lung function, adapt, suggesting changes in central nervous system signaling. We determined whether repeated ozone exposures altered the behavior of nucleus tractus solitarius (NTS) neurons where reflex respiratory mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…tive stress that disrupts breathing, particularly in children, increased R in and depolarized monkey NTS neurons (11). Together, these observations suggest that the effects of oxidative stress on respiration could be, in part, mediated by CO 2 /H ϩ -chemosensitive SC neurons.…”
Section: Oxidative Stress Excites Putative Co2/hmentioning
confidence: 82%
“…tive stress that disrupts breathing, particularly in children, increased R in and depolarized monkey NTS neurons (11). Together, these observations suggest that the effects of oxidative stress on respiration could be, in part, mediated by CO 2 /H ϩ -chemosensitive SC neurons.…”
Section: Oxidative Stress Excites Putative Co2/hmentioning
confidence: 82%
“…Airways function in response to stimuli, including irritants, allergens, and inflammatory mediators. Chen et al 19,20 have demonstrated the ability of the nucleus tractus solitarius, a CNS region containing neurons that process lung sensory signals, to undergo marked changes in excitability in the face of extended exposure to irritants (ie, allergen exposure, ozone exposure, and tobacco smoke). These toxicants share commonalities in the responses they may illicit in the airways (eg, local release of inflammatory mediators, oxidative stress, and activation of sensory neurons) that may contribute to the respiratory inflammatory and motor response.…”
Section: Stress and Autonomic Control Of Airwaysmentioning
confidence: 99%
“…NTS neurons that receive afferent inputs from lung and tracheal receptors exhibit exaggerated responses to stimulation of airway receptors following chronic exposures to airway pollutants (eg, cigarette smoke) [12]. NTS neurons recorded in a brain-slice preparation from infant primates episodically exposed to ozone for 14 days exhibited a decreased tendency to respond to synaptic activation coupled with an increased intrinsic excitability [13]. Chronic exposure to hypoxia (7 days at 10% oxygen) induces the opposite changes in NTS neurons receiving arterial chemoreceptor inputs: an increased response to synaptic excitation and a reduced intrinsic excitability (Zhang and Mifflin, Unpublished data).…”
Section: Nucleus Of the Solitary Tractmentioning
confidence: 99%